1978
DOI: 10.1002/chin.197827087
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: THERMOLYSIS OF 2‐ACETOXY‐Δ3‐1,3,4‐OXADIAZOLINES. EVIDENCE FOR STEPWISE HOMOLYSIS OF CYCLIC DIAZENES

Abstract: Die Thermolyse der Titelverbindungen (I) ergibt statt der erwarteten Epoxide vom Typ (V) die Ether (II) als Hauptprodukte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Warkentin and co-workers (26)(27)(28)(29)(30)(31)(32)(33)(34) have shown that a series of 3 triazolines (12)(13)(14) gives exclusive 3-piece fragmentation, whereas iminooxadiazoline 15 N-P: and oxadiazolinone 16 demonstrate competing in-data for appropriate model compounds to estimate dependent mechanisms for 1,3-dipolar cycloreversion thermodynamic quantities of interest for these and 3-piece fragmentation. In examining these diazenes and their reactions.…”
Section: Thermal Fragmentation Patterns Of 5-memberedmentioning
confidence: 99%
See 1 more Smart Citation
“…Warkentin and co-workers (26)(27)(28)(29)(30)(31)(32)(33)(34) have shown that a series of 3 triazolines (12)(13)(14) gives exclusive 3-piece fragmentation, whereas iminooxadiazoline 15 N-P: and oxadiazolinone 16 demonstrate competing in-data for appropriate model compounds to estimate dependent mechanisms for 1,3-dipolar cycloreversion thermodynamic quantities of interest for these and 3-piece fragmentation. In examining these diazenes and their reactions.…”
Section: Thermal Fragmentation Patterns Of 5-memberedmentioning
confidence: 99%
“…The heat of formation of dimethyl a-lactone (18) is estimated in eq. [14], leading to a reaction enthalpy of -2 kcal for 3-membered ring formation. The differences between 166 and 16a were set equal to the difference between 15b and 15a (next section).…”
Section: Oxadiazolinone Idamentioning
confidence: 99%